Arduino Uno Based Automatic Water Faucet with Ultrasonic Sensor - Arifudin Arifudin; Muhamad Soleh; Erfan Subiyanta (Mestro, 2021)
Water is a source of life for all living things. However, currently the amount of clean water available is very limited so that it is not comparable with the increasing growth of the world's population. The saving effort that can be done is to make the best use of water. One of them is by saving bath water by controlling the water level in the water reservoir. In this final project, an automatic faucet is designed using an ultrasonic sensor, namely a sensor that will detect the presence of an object and remove or turn off water automatically with the main actuator using a servo motor. In filling the water reservoir to prevent water from overflowing, an ultrasonic sensor is used which will automatically fill when the water volume distance is not within the specified range and will also automatically stop filling when it is within the specified range. So that no more water is wasted due to user negligence.